Situated learning in science education: socio‐scientific issues as contexts for practice - Sadler, Troy D. (Studies in Science Education, 2009)
This paper presents situated learning as a theoretical framework for conceptualising new ways to approach science education. Key constructs associated with this framework, including communities of practice, Discourse and identity, are introduced. I advance an argument to develop classroom communities of practice based on engaged citizenship relative to the negotiation of socio‐scientific issues (SSI). The aim of this approach would be student development of practices and dispositions that better prepare them for active participation in society, particularly in the context of science‐related social issues. Extant literature regarding the effects of SSI interventions is reviewed and synthesised to explore the extent to which the articulated vision has been enacted and to better understand affordances and constraints associated with this enactment. Twenty‐four studies are examined that meet criteria including recency, a focus on empirical investigations of SSI interventions and research rigor. The results of these research reports are categorised in an emergent taxonomy of findings with the following major categories: interest and motivation, content knowledge, nature of science, higher‐order thinking and community of practice. Finally, the paper explicitly considers the value of framing SSI based research and practice in terms of a situated learning perspective.